The Ecotheological Movement of the Muhammadiyah Environmental Council in Response to the Environmental Governance Crisis - Setiawan, Hendy; Kurniawan, Nanang Indra; Santoso, Purwo (Millah: Journal of Religious Studies, 2022)
This article describes the ecotheological movement of the Muhammadiyah Environmental Council (Majelis Lingkungan Hidup abbreviated MLH in Bahasa Indonesia) in response to the environmental crisis. The birth of the ecotheological movement in Muslim communities such as Muhammadiyah is a new awareness in the Islamic world. This is because, so far, the issues of environmental crisis have only grown and developed in the world of self-help (secular organizations). As a result, it raises the question of how the role of religion, more precisely the Muslim community, has tended to be passive in responding to environmental crises. Therefore, the spirit of Al-Ma'un's theology at Muhammadiyah in recent years has begun to find its relevance in identifying the environment as ecotheology. The research method used in this research is descriptive and qualitative, which aims to understand the ecotheology movement in MLH. Liberation theology theory (Gustavo Guiterez) and ecotheology are used to analyze the environmental movement in this Muslim community. The findings of this study explain that the ecotheology movement at MLH was born as a manifestation of the theology of Al-Ma'un 1912, which, one century after its birth, has not responded to the issue of environmental damage. However, since the liberation theology of the 1980s has become a global narrative, KH Ahmad Dahlan's theology has found its relevance and pioneered the religious community movement. The involvement of these groups, such as MLH, is a new chapter in how religion is relevant in bringing theological messages that have not been seen so far.